Development of a PC-based electropalatograph system for speech therapy - Sudirman, Rubita; Yunus, Jasmy (Faculty of Electrical Engineering, 2002)
People who have difficulties with speech can learn to pronounce word more clearly by using electropalatograph (EPG). The EPG is a device that uses an artificial palate worn against the roof of the mouth, which is able to detect tongue contact and enable the analysis of these contact patterns. The tongue contact is displayed on PC screen in tongue-palate contact pattern. By watching the tongue contact and comparing it with standard tongue positions, people with impaired speech can learn how to shape different sounds.